Audiovisual Media Based on Tapai Singkong Local Wisdom in Project-Based Learning for Science Concept Understanding, Environmental Care Attitudes, and SDGs - Nurliza; Sri Winarni; A. Halim; Rahmad Rizki Fazli; Richa Purmayasari (Postgraduate, University of Mataram, 2026)
Science instruction in many schools remains verbalistic and disconnected from students' everyday experiences, limiting conceptual understanding and environmental care attitudes. This study examined the effectiveness of audiovisual-based learning grounded in local wisdom for improving science concept understanding and environmental care attitudes among ninth-grade students at SMP Negeri 3 Singkohor, Aceh Singkil, using a sequential explanatory mixed-methods design. A one-group pretest-posttest design was applied to ten students using a validated 20-item multiple-choice instrument, followed by a qualitative phase with six purposively selected students representing high, medium, and low conceptual gain, examined through participatory observation, interviews, and documentation. The average score rose from 61.00 to 91.50, yielding an N-Gain of 0.79 (high category), though the small sample limits statistical generalization. Qualitative findings showed local wisdom bridged abstract concepts, and environmentally responsible behaviors emerged spontaneously at school, though this awareness did not consistently extend to plastic use at home. These results suggest that local-wisdom-based audiovisual learning can strengthen conceptual understanding and environmental awareness, while broader application warrants further testing.